Exploring the neurocognitive basis of language processing: the case of word classes and the key role of interface semantics (Atti del Sodalizio Glottologico Milanese, 2019)
In the present paper, we address the question of the linking mechanisms of the multifactorial and graded conceptual space with the formally discrete language structures by 1) investigating the neurocognitive basis of interface semantics and 2) exploring the representation of word classes in the brain. Data from cognitive neuropsychological and brain imaging studies are discussed, and an answer is provided to certain critical aspects of the relationship between conceptual categorization and linguistic categorization. KEYWORDS: Conceptual categorization, linguistic categorization, interface semantics, word classes, cognitive neuropsychology, fMRI